Perkembangan Jumlah Pelaku Usaha, Asset dan Jumlah Tenaga Kerja di Kota Magelang tahun 2016-2019 - DWI NUR LESTARI (JURNAL EKOMBIS, 2021)
Micro, Small and Medium Enterprises have an important role in economic growth, one of which is to absorb labor. the number of businesses is increasing and the increase in assets and the number of unemployment is declining. This study aims to find out how the development of the number of business actors and assets towards the absorption of umkm workforce in the City of Magelang. The data used are secondary data from 2016-2019 in the form of variables in the number of business actors, assets and labor. While the method used is descriptive analysis method. The results of this study indicate that there is a decrease in the employment of MSMEs in the City of Magelang